The Influence of Social Media, E-Service, And Brand Image to Satisfaction Customer Use Travelio In Order Accommodation - Kristia Kristia; Meylani Tuti (ProBisnis : Jurnal Manajemen, 2023)
Study This aim for investigate the impact of social media, e-services, and image brand to satisfaction customer moment use service booking accommodation Travelio. The population involved in study This is visitor Travelio. The sampling method used is accidental sampling with a total of 149 respondents. Deep data analysis study This using the Structural Equation Model with use method analysis quantitative namely Partial Least Square (PLS) 3.0. Research results show that there is influence positive social media to satisfaction customer in order accommodation through Travelio. Besides that, e-service also has influence positive to satisfaction customer in order accommodation through Travelio. Next, image brand also matters positive to satisfaction customer in order accommodation through Travelio. More further, satisfaction customer in order accommodation through Travelio influenced in a manner together by social media, e-service, and imageÂ brand.